Teknik Budidaya Rumput Laut (Gracilaria verrucosa) Dengan Metode Rawai Di Balai Budidaya Air Payau Situbondo Jawa Timur [Technique Of Seaweeds Culture (Gracilaria verrucosa) At Brackish Water Aqua Culture Development Center Situbondo Of East Java] - Rahayu Kusdarwati; Istiqomawati Istiqomawati (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
AbstractSeaweeds is one of commodities fishery sector have commercial value, so that it has been culturing by seaweeds farmer. Technique of seaweeds culture is one of the aim concept for successfully culture it. The aim of this case study is to get about technique culture, culture, maintain of microbe and disease, post harvesting, marketing and the effort analysis at Brackish water Aquiculture Development Center Pulokerto Countryside Kraton Sub District Pasuruan Regency and Province of East Java. The case study was held on August 4 to September 17 2008. The work method was using in this case study was descriptive method by taking data's technique by participate actively, observation, interview and the literature study. Seaweeds culture company at Brackish water Aquiculture Development Center Pulokerto Countryside Kraton Sub District Pasuruan Regency and Province of East Java is property of Blackish water Aquiculture Development Center Situbondo Sub Division Seaweeds culture, have the culture area was at pond with wide 36 hectare (Ha) with 38 cabin and each cabin width 0,5 hectare (Ha), with condition of bottom sea were companing a sand muddy. Water quality measuring at location were; pH 7 – 8, salinity 35 – 37,5 ppt, temperature 25,7 – 29,6°C, and disolved oxygen 4,32 – 5,79 mg/l. Cultivation technique of seaweeds using long line methods. The size raft is 100 m, using ris rope PE 3 mm. The cultivation distance between ris rope 3 – 5 m, while for seed is a 25 cm. Seed stocking was conduct on directly. Cultivation of seed was in the morning or in the evening with 20 – 25 day age of seed. Harvesting of seaweed was using 2 models were pluck up crop and all crop. Post harvesting of seaweed is going to washed, dried afterward directly selling of dry seaweed. Harvest product seaweed the big part selling at factory among others at Agar Sehat Factory at Purwosari Pasuruan, Indo Flora Factory at Bandulan Malang, Sriti Factory at Pandaan Pasuruan and Sri Gunting Factory at Lawang Malang, with price for factory 2.500/kg but for farmer 2.000/kg.